Pengaruh Gaya Kepemimpinan dan Disiplin Kerja terhadap Kinerja Pegawai pada Kantor Badan Penanggulangan Bencana Daerah Provinsi Sumatera Utara - Habib Ridho Pratama (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2020)
The purpose of this study was to determine and analyze the effect of leadership style and work discipline partially and simultaneously on the performance of employees at the Office of the Regional Disaster Management Agency of North Sumatra Province. Samples were selected using the random sampling method with the Slovin formula. Data is processed using multiple linear regression statistical test methods. The results of this study prove that leadership style has a significant effect on employee performance at the Office of the Regional Disaster Management Agency of North Sumatra Province. Likewise, the work discipline that affects the performance of employees at the Office of the Regional Disaster Management Agency of North Sumatra Province. The leadership style and work discipline simultaneously influence the performance of employees in the Office of the Regional Disaster Management Agency of North Sumatra Province.